Characterization of reduced graphene oxide anode for application in algae biophotovoltaic platforms / Siti Aisyah Ibrahim - Siti Aisyah , Ibrahim (2020)
Research interest in recent times has placed much focus on electrode technology for biophotovoltaics (BPV) especially in algal fuel cells (AFCs) application. The purpose of this investigation is therefore directed towards optimizing reduced graphene oxide (rGO) thin film as an electrode for AFCs application by means of annealing and plasma treatment. First stage involves deposition of six (6) layers of rGO thin film using Langmuir-Blodgett (LB) method. The anode electrodes were then annealed at different temperatures under vacuum condition. For plasma treatment meanwhile, a variation of voltage was used to vary the plasma conditions resulting in different surface morphology. To characterize the multilayer films fabricated, the thin films were characterized by means of spectroscopic, structural and electrical studies. In general, results indicate improvement in conductivity and wettability test, which may prove beneficial for implementation in AFCs, and promote improved algae growth, adhesion and photosynthesis yield as an outcome of higher charge mobility.